Biological behavior of preneoplastic conditions of the endometrium: A retrospective 16-year study in south India - Rao Shalinee; Sundaram Sandhya; Narasimhan Raghavan (Indian Journal of Medical and Paediatric Oncology)
Background: The biological behavior of endometrial carcinoma differs in epidemiology, presentation, and prognosis, suggesting that there are two fundamentally different pathogenic types of disease: type I (estrogen related, endometrioid type) and type II (non-estrogen related, non-endometrioid type). Untreated hyperplasia can develop into an endometrioid type of adenocarcinoma, hence, it is important to recognize the former type. In contrast to cervical cancers, there are limited studies with respect to the biology of hyperplastic lesions documented from India. This was a 16-year retrospective study, carried out to determine the nature and outcome of proliferative lesions of the endometrium in a referral center from south India. Materials and Methods: A histopathological diagnosis of the endometrial hyperplasia, polyp, and carcinoma, on endometrial biopsy and hysterectomy specimens, over a 16 year period (1983 to 1999), were recorded in a computer and the case slides were reviewed. Using the computer software Foxpro, the patients who had come more than once for a subsequent or previous biopsy were identified. An attempt was made to look for progression, regression or a static nature of the lesion in the follow-up cases. Results: A total of 1778 cases were studied, and only 74 patients with endometrial hyperplasia and five cases of benign endometrial polyp had follow-up endometrial histopathology. Hyperplasia cases included 59 cases of simple hyperplasia, 10 cases of complex hyperplasia without atypia, and five cases with atypia. The predominant age for patients with all types of hyperplasias was 41 - 50 years. Progression to a higher grade was seen in 8.10%, regression to a lower grade was seen in 9.45%, lesions reverted to a normal pattern in 10.81% cases, and lesions persisted in 70.27% of the cases. A mixed pattern was seen in 54 cases, with predominant coexistent lesion being simple and complex hyperplasia without atypia. Conclusion: The fate of the hyperplastic lesion of the endometrium showed a varied pattern. Follow-up cases predominantly showed persistence of the lesion, possibly resulting from a fluctuating but higher level of estrogenic stimulus. Hence, it was not only the high levels of estrogen that influenced the biology, but its sustenance for a prolonged period.